Kriminalisasi dalam Ketentuan Pidana Pemberian ASI Eksklusif Ditinjau dari Perspektif Keadilan Pancasila - Windayani, Tisa (Universitas Negeri Malang, 2023)
This study aims to describe the internalisation of justice based on Pancasila in the concept of criminalization and analyse the criminal provisions of the exclusive breastfeeding program from the perspective of criminalization based on Pancasila justice. This study is included in normative legal research. The results of the study show that the handling of criminalization must be in accordance with the concept of justice from the Pancasila perspective which contains two main elements, namely proportionality and the principle of kinship to maintain unity. The crime of exclusive breastfeeding programs is related to the denial of obligations carried out by families or corporations to provide time and facilities to support exclusive breastfeeding. Criminal sanctions for actions that do not support the implementation of the exclusive breastfeeding program in the form of imprisonment, fines or additional penalties as regulated in Article 430, Article 447 and Article 448 of Law Number 17 of 2023 are not in accordance with the concept of justice based on the Pancasila perspective because they do not meets the aspect of proportionality and does not reflect the principle of kinship.